# how do you start this equation i've been tryng it for 20min.

sec^6x(secxtanx)-sec^4x(secxtanx)=sec^5xtan^3x

ec^6x(secxtanx)-sec^4x(secxtanx)=sec^5xtan^3x

Factor out a sec^5 tan and divide thru. Left is

sec^2 x = Tan^2 x

Then this should reduce to

sin^2 x = cos^4 x

take the square root of each side

sin x= cos^2 x

change the cos squared to 1-sin^2

sin^2 x + sin x -1=0

Now you have a quadratic, use the quadratic equation.

## To solve the equation sec^6x(secxtanx)-sec^4x(secxtanx)=sec^5xtan^3x, we can follow these steps:

Step 1: Simplify the equation by factoring out sec^5xtanx on the left side:

sec^5xtanx(secxtanx) - sec^4x(secxtanx) = sec^5xtan^3x

Step 2: Divide both sides of the equation by secxtanx:

sec^5xtanx - sec^4x = sec^5xtan^2x

Step 3: Cancel out the sec^5xtanx term on both sides:

- sec^4x = sec^5xtan^2x

Step 4: Rewrite the equation using trigonometric identities:

(sec^2x)(- sec^2x) = (sec^2x)(tan^2x)

Step 5: Simplify the equation further:

-sec^4x = sec^2xtan^2x

Step 6: Convert sec^4x to its equivalent in terms of sin and cos:

- (1/cos^4x) = (1/cos^2x)(sin^2x)

Step 7: Multiply both sides of the equation by cos^4x:

-1 = sin^2xcos^2x

Step 8: Use the Pythagorean Identity sin^2x + cos^2x = 1 to rewrite the equation:

-1 = (1 - cos^2x)cos^2x

Step 9: Distribute and rearrange the equation:

-1 = cos^2x - cos^4x

Step 10: Move all the terms to one side of the equation to form a quadratic equation:

cos^4x - cos^2x -1 = 0

At this point, we have a quadratic equation in terms of cosx. To solve this equation, you can use the quadratic formula or factoring. I will show you how to use the quadratic formula:

Step 11: Apply the quadratic formula:

cosx = [-b ± √(b^2 - 4ac)] / (2a)

For the equation cos^4x - cos^2x - 1 = 0, we have:

a = 1, b = -1, c = -1

cosx = [-(-1) ± √((-1)^2 - 4(1)(-1))] / (2(1))

Simplifying this expression will give you the values of cosx. Remember that cosx can range from -1 to 1, so you should check each solution within that range to find the valid solutions for x.

Note: If you want the exact values of cosx, you may need to further simplify the expression and use trigonometric identities or a calculator to find the values.